Tlx3 Exerts Direct Control in Specifying Excitatory Over Inhibitory Neurons in the Dorsal Spinal Cord - Monteiro, Filipe A.; Miranda, Rafael M.; Samina, Marta C.; Dias, Ana F.; Raposo, Alexandre A. S. F.; Oliveira, Patrícia; Reguenga, Carlos; Castro, Diogo S.; Lima, Deolinda (Frontiers in Cell and Developmental Biology, 2021)
The spinal cord dorsal horn is a major station for integration and relay of somatosensory information and comprises both excitatory and inhibitory neuronal populations. The homeobox gene Tlx3 acts as a selector gene to control the development of late-born excitatory (dILB) neurons by specifying glutamatergic transmitter fate in dorsal spinal cord. However, it is not known how Tlx3 functions to promote excitatory cell fate, given its direct transcriptional targets remain largely unknown. Here we combined a genomics approach based on chromatin immunoprecipitation followed by next generation sequencing (ChIP-seq) and expression profiling, with validation experiments in Tlx3 null embryos, to characterize the transcriptional program of Tlx3 in mouse embryonic dorsal spinal cord. We found most dILB neuron specific genes previously identified to be directly activated by Tlx3. Surprisingly, we found Tlx3 also directly represses many genes associated with the alternative inhibitory dILA neuronal fate. In both cases, direct targets include transcription factors and terminal differentiation genes, showing that Tlx3 directly controls cell identity at distinct levels. Our findings provide a molecular frame for the master regulatory role of Tlx3 in developing glutamatergic dILB neurons. In addition, they suggest a novel function for Tlx3 as direct repressor of GABAergic dILA identity, showing how generation of the two alternative cell fates are tightly coupled.